"Football is pure enjoyment": An exploration of the behaviour change processes which facilitate engagement in football for people with mental health problems. (March 2019) - Hargreaves, Jackie; Pringle, Andy
Abstract: Introduction: Physical activity is known to be beneficial for people with mental health problems, although engagement is low. Football, provided by professional football club community trusts could aid engagement in physical activity, however little is known about the behaviour change processes which engage individuals in this type of PA. One factor which is often overlooked is affect and exploring this could help identify the behaviour change processes, which engage individuals in a professional football club-led mental health intervention. The aim of this study was to explore the experiences of individuals attending football provided by a professional club community trust to further our understanding of the behaviour change processes involved in facilitating engagement in this provision. Method: Semi-structured interviews were conducted with twelve men who played football provided by a professional football club trust. A range of mental health problems were reported and the participants were aged between 19 and 46. Template analysis was conducted, implementing some of the concepts from the Affective – Reflective Theory (ART). Results: The results highlighted that both affective and reflective processes of ART were evident in engaging individuals in football. Pleasurable experiences were enabled through the physical and social characteristics of football. Self-control strategies emerged which help to action engagement. The professional football club trust provided coaching knowledge and skills, team organisation and resources and feelings of belonging and responsibility. Conclusion: Application of ART to the understanding of football experiences has provided a novel exploration of the processes involved in engaging individuals in football. This has important implications for intervention design; the focus should be on providing pleasurable experiences and fostering appropriate self-control strategies. Highlights: Delivery by a professional football team enhanced a sense of belonging. Social support, self-talk and striving for a group goal aided engagement. The intensity, self development and social environment influences enjoyment of football. Affective-reflective theory can help to understand engagement in football.